2009
DOI: 10.1159/000228930
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Unaided Smoking Cessation after Deep Brain Stimulation of the Nucleus Accumbens

Abstract: Aims: We explore whether clinical research on deep brain stimulation (DBS) of the nucleus accumbens (NAc) to treat addiction is justified besides theoretical speculation. Methods: Since 2004, 10 patients who were also smokers were treated at the University of Cologne for Tourette’s syndrome (TS), obsessive-compulsive disorders (OCD) or anxiety disorders (AD) by DBS of the NAc. We assessed their smoking behavior after DBS and (in retrospection) before by the Fagerström Test for Nicotine Dependence (FTND) and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(96 citation statements)
references
References 29 publications
1
90
0
2
Order By: Relevance
“…Fortuitous observations of improvements in alcoholism [125], nicotine [126][127][128] or food addiction [128] have been reported for patients treated with NAcc DBS for anxiety, OCD or GTS. Three patients were treated with NAcc DBS specifically for alcohol addiction.…”
Section: Reviewmentioning
confidence: 99%
“…Fortuitous observations of improvements in alcoholism [125], nicotine [126][127][128] or food addiction [128] have been reported for patients treated with NAcc DBS for anxiety, OCD or GTS. Three patients were treated with NAcc DBS specifically for alcohol addiction.…”
Section: Reviewmentioning
confidence: 99%
“…Of the latter 4, 2 attempted and were successful at smoking cessation after DBS. 100 Several preclinical studies in rats have investigated the effect of high-frequency DBS on ethanol consumption and cocaine/narcotic-seeking behavior. 15,79,92,165,193 These studies showed a significant reduction in drugseeking behaviors following DBS.…”
Section: Addictionmentioning
confidence: 99%
“…The mesolimbic dopamine system plays a central role in brain reward mechanisms with the nucleus accumbens (NAc) serving as a key structure in mediating these effects [7][8][9][10]. Based on this understanding, some functional neurosurgeons have used ablation or stimulation of the NAc to effectively treat severe refractory cases of obsessive-compulsive disorders and depression [11][12][13][14][15][16][17][18][19][20][21]. These patients incidentally noted decreases in chemical dependence [15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this understanding, some functional neurosurgeons have used ablation or stimulation of the NAc to effectively treat severe refractory cases of obsessive-compulsive disorders and depression [11][12][13][14][15][16][17][18][19][20][21]. These patients incidentally noted decreases in chemical dependence [15][16]. In parallel, a series of Chinese animal studies suggested the utility of NAc lesioning in treating drug dependence [22], which led to initial trials in humans in China with reasonable efficacy [11].…”
Section: Introductionmentioning
confidence: 99%